A randomized, 12-month, parallel-group trial testing the effects of a cognitive behavioral healthy lifestyle intervention as an adjunct to standard trauma therapy among adults with PTSD: the I-CHAT study protocol - Kibler, Jeffrey L.; Owney, Abigail; Rosado, Carolina; Murphy, Shalynn; Llabre, Maria Magdalena; Molina Valenzuela, Karla Patricia; Ocholski, Claudia; Ma, Mindy (Frontiers in Psychology, 2025)
Research has indicated strong associations between posttraumatic stress and cardiovascular disease (CVD) risk. Individuals with posttraumatic stress disorder (PTSD) tend to show patterns of elevated CVD risk earlier in life than the general population. The need for developing effective interventions for CVD risk-reduction in PTSD is increasingly evident. The present paper outlines the theoretical background and methodological details for the protocol of an ongoing NHLBI-funded longitudinal study (entitled Investigating Cardiac Health of Adults with Trauma) to test the effects of a health behavior intervention as an adjunct to standard trauma therapy in PTSD. The health behavior intervention addresses CVD-related health behaviors (physical activity, nutrition, sleep, and stress). Participants are randomized to the health behavior intervention plus standard trauma therapy condition or a standard trauma therapy control group. Outcome assessments are conducted before and after the 12-week intervention program in the experimental group, and 12 weeks apart for the control group, as well as at 6-month and 12-month follow-up time points. The outcomes include laboratory measures of CVD risks/markers (e.g., endothelial function, arterial stiffness, lipids, blood pressure), actigraphy-based measures of physical activity and sleep, and standardized self-report measures of sleep, physical activity, nutrition, stress, and psychological functioning (e.g., PTSD symptoms, depressive symptoms). The study findings will provide valuable data on the effectiveness of the health behavior intervention in producing predicted changes in the target CVD-related behaviors/markers.